2016
DOI: 10.1261/rna.057448.116
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function analysis and genetic interactions of the SmG, SmE, and SmF subunits of the yeast Sm protein ring

Abstract: A seven-subunit Sm protein ring forms a core scaffold of the U1, U2, U4, and U5 snRNPs that direct pre-mRNA splicing. Using human snRNP structures to guide mutagenesis in Saccharomyces cerevisiae, we gained new insights into structure-function relationships of the SmG, SmE, and SmF subunits. An alanine scan of 19 conserved amino acids of these three proteins, comprising the Sm RNA binding sites or inter-subunit interfaces, revealed that, with the exception of Arg74 in SmF, none are essential for yeast growth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
(45 reference statements)
1
14
0
Order By: Relevance
“…Given the conservation from yeast to humans of the core Sm ring structure and the shared principle of RNA recognition via an amino acid triad present in each Sm subunit, one might have expected the Sm protein-RNA complex to be functionally acutely sensitive to perturbations of the protein-RNA interface and/or Sm-Sm subunit interface. This is clearly not the case in budding yeast, insofar as only two of 54 alanine mutations were lethal (Schwer and Shuman 2015;Schwer et al 2016Schwer et al , 2017. Lethal single-alanine mutations were confined to the RNA-binding sites of SmD1 (Arg88) and SmD2 (Arg97), thus highlighting the unique importance of their π-cation interactions with the sixth and seventh nucleobases of the Sm RNA site, respectively.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Given the conservation from yeast to humans of the core Sm ring structure and the shared principle of RNA recognition via an amino acid triad present in each Sm subunit, one might have expected the Sm protein-RNA complex to be functionally acutely sensitive to perturbations of the protein-RNA interface and/or Sm-Sm subunit interface. This is clearly not the case in budding yeast, insofar as only two of 54 alanine mutations were lethal (Schwer and Shuman 2015;Schwer et al 2016Schwer et al , 2017. Lethal single-alanine mutations were confined to the RNA-binding sites of SmD1 (Arg88) and SmD2 (Arg97), thus highlighting the unique importance of their π-cation interactions with the sixth and seventh nucleobases of the Sm RNA site, respectively.…”
Section: Introductionmentioning
confidence: 97%
“…The remarkable tolerance of the seven yeast Sm proteins to mutations of the amino acids at their RNA interfaces or protein-protein interfaces suggested that the Sm ring system has built-in redundancy. To comprehensively address this issue, we conducted an "all-against-all" test of 406 different pairwise combinations of structure-guided mutations in any two of the Sm ring subunits, which unveiled a wide network of 137 intersubunit synthetic lethalities (Schwer and Shuman 2015;Schwer et al 2016Schwer et al , 2017. A key conclusion was that five of seven intact RNA-binding sites in the Sm ring do not suffice for in vivo function.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, for SmF, SmE, SmG, SmD3, and SmB, as for so many components of the S. cerevisiae spliceosome, the effects of perturbing protein-RNA and protein-protein interactions were masked in an otherwise wild-type genetic background because of inherent functional redundancies of the yeast splicing machine. Our survey of genetic interactions with multiple non-Sm splicing factors showed that mutations of SmG, SmE, SmF, SmD3, and SmB consistently elicited synthetic lethality in the absence of U2 snRNP subunits Lea1 and Msl1 (Schwer and Shuman 2015;Schwer et al 2016). Sporadic synergies of specific Sm mutations were observed absent other early spliceosome components: Mud1, Nam8, Mud2, and TMG caps.…”
Section: Introductionmentioning
confidence: 89%
“…Crystal structures of the human Sm ring and its RNA interface with U1 and U4 snRNAs are known (Kambach et al 1999;Weber et al 2010;Kondo et al 2015;Li et al 2016), and recent cryo-EM studies of splicing complexes are providing similar insights into the budding and fission yeast Sm rings (Hang et al 2015;Nguyen et al 2015;Galej et al 2016;Wan et al 2016a,b;Yan et al 2016). We have married these advances in snRNP structural biology to the genetics of budding yeast to elucidate structure-function relationships and genetic interactions of the essential Sm ring subunits SmF, SmE, SmG, SmD3, and SmB (Schwer and Shuman 2015;Schwer et al 2016).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation